Uczeń z doświadczeniem migracji w edukacji. Diagnoza potrzeb i obszary wsparcia w ramach edukacji włączającej – uczeń cudzoziemski - Chrzanowska, Iwona; Jachimczak, Beata (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
The text is dedicated to the subject of support in education involving one of the groups of students with special educational needs - foreign students. Compared to other groups of pupils from the SPE, it is a small population of students in Poland. It represents less than 0.4% of students with special educational needs. The problems of foreign pupils, both in relation to education and social integration in the country they came to, are specific even within the group of pupils from the SPE. However, as the research results on the issue indicate, among others due to the small population of foreign pupils in Poland, teachers regard the problem of social inclusion of immigrant pupils as hypothetical, unrealistic. According to the concept of inclusive education, it is assumed that support in development is to be dedicated to all students regardless of whether they constitute a group: easily identifiable as part of the current categorical approach to the diagnosis of needs, numerous or less numerous, with permanent and serious development disorder or less serious problems, requiring only temporary support and small adjustments. In each case, however, it is necessary to diagnose the needs not only of students and their families, but also teachers and educational staff to introduce systemic changes, so that the support is no longer stigmatizing for the student, and was associated with selfacceptance, self-awareness and the desire to maximize predisposition and developmental potential of a person.